Analysis of the Implementation of Policies and Programs by the Situbondo Regency Government in Efforts to Reduce Early Marriage Rates - Fatimatuz Zahro; Busriyanti Busriyanti; Muhammad Faisol (Academia Open, 2025)
General Background: Early marriage remains a persistent social problem in Indonesia, contributing to educational discontinuity, psychological vulnerability, health risks, and weakened family resilience. Specific Background: In Situbondo Regency, despite stricter legal frameworks and the implementation of multiple preventive programs by the local government, marriage dispensation cases remain relatively high, indicating implementation challenges. Knowledge Gap: Previous studies have largely focused on the causes and impacts of early marriage, while limited attention has been given to in-depth analysis of how local government policies and programs are implemented and what factors shape their effectiveness. Aims: This study aims to analyze the implementation of early marriage prevention policies and programs by the Situbondo Regency Government and to identify supporting and inhibiting factors influencing their outcomes. Results: Using a qualitative empirical approach, the findings show that programs such as PERAK CINTA, BRUS, BINWIN, premarital health checks, psychological counseling, and cross-sector coordination have been implemented with clear objectives and structured mechanisms, yet their effectiveness is constrained by limited resources, uneven communication, strong cultural norms favoring early and unregistered marriages, and low community awareness. Novelty: This study integrates policy implementation analysis with local socio-cultural dynamics using the Van Meter and Van Horn framework in the context of early marriage prevention. Implications: Strengthening budget allocation, community education, and cross-sector synergy is essential to enhance the effectiveness and sustainability of early marriage prevention policies at the local level. Highlights: Policy Execution: Early marriage prevention policies are implemented through structured, cross-sector programs with clear operational mechanisms. Implementation Barriers: Cultural norms, limited resources, and low community awareness significantly constrain policy effectiveness. Strategic Implication: Strengthening community engagement and inter-agency coordination is crucial for sustainable prevention outcomes. Keywords: Early Marriage, Policy Implementation, Local Government, Prevention Programs